Роль малого бизнеса в развитии экономики России (Путеводитель предпринимателя)
The scientific publication examines the role of small business, its advantages and disadvantages in the economic development of Russia. Fairly in detail the problems of supporting small business are disclosed in the article. The author gives comparative analysis of the development of small businesses in Russia and abroad. On the basis of the conducted study the author of the article suggests certain measures to improve the state support for SME development in Russia’s economic modernization.